Plasma modified attapulgite / carbon composite material as well as preparation method and application thereof

By modifying the concave and convex rod/carbon composite materials, the adsorption and catalytic performance are improved, and the problem of removing pollution of multiple metals and organic matter in complex wastewater is solved, and efficient and environmentally friendly pollution removal effect is achieved.

CN119657083APending Publication Date: 2025-03-21HUNAN AGRI UNIV
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202510025850.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove the coexisting pollution of multiple heavy metals and organic matter in complex wastewater, and traditional methods have problems of secondary pollution and environmental impact.

Method used

By plasma modification of the concave and convex rod/carbon composite material, it improves its adsorption effect on metal ions and is used as a catalyst in an advanced oxidation system to avoid dissolution of metal ions and reduce the risk of secondary contamination.

Benefits of technology

It achieves efficient removal of a variety of heavy metals and organic matters, improves catalytic efficiency, reduces the risk of desorption of heavy metals, and provides an effective co-removal method suitable for complex wastewater treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657083A_ABST
    Figure CN119657083A_ABST
Patent Text Reader

Abstract

The invention discloses a plasma modified attapulgite / carbon composite material as well as a preparation method and application thereof. The preparation method comprises the following steps: S1, preparing a preliminarily activated attapulgite / carbon composite material; and S2, performing plasma treatment. The composite material is simple in preparation method, has good adsorption performance on heavy metals in wastewater, and can be used as an adsorbent for wastewater containing heavy metals, and the composite material adsorbing the heavy metals can be directly used as an adsorbent and a catalyst for degrading levofloxacin in a PDS system. The composite material has the advantages of high catalytic efficiency, high degradation rate and no secondary pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysts, and more specifically, relates to a plasma-modified attapulgite / carbon composite material and a preparation method and application thereof. Background Art

[0002] Studies have shown that wastewater has a complex composition and it is difficult to effectively treat water pollution using simple removal methods. Another common phenomenon in wastewater is that multiple pollutants interact with each other to form a stable structure, which poses great difficulties for us to solve the problem of wastewater pollution. For example, heavy metals will form complexes with organic matter. Unfortunately, this complex has a stable structure with steric hindrance and is widely present in the water environment, but it is easy to be overlooked. Strong ligands can act as armor to protect heavy metals from "harm", making the removal of target pollutants more complicated and difficult.

[0003] In recent years, more and more scholars have devoted themselves to studying the use of adsorption, photocatalysis, Fenton, electrocatalysis or advanced oxidation to treat pollutants in water. For example, Peng Yu et al. used advanced oxidation technology to efficiently remove Cu (II) and HCIP. Shui Yu Zuo used photocatalysis / PMS to degrade CIP. However, photocatalysis and electrocatalysis technologies cannot be used on a large scale due to conditions, and Fenton treatment will cause a large amount of iron sludge to accumulate, which is easy to cause secondary pollution to the environment. Advanced oxidation and adsorption methods are green and efficient and are deeply loved by researchers. At present, research is mainly focused on materials for efficient removal of heavy metals or organic matter, and there is little research on the relationship between multiple heavy metals and organic matter when they coexist. Most studies are aimed at a specific pollutant or a single heavy metal and organic matter composite pollution. However, in actual wastewater, multiple heavy metals and organic matter often coexist, which makes the water environment more complicated. Therefore, developing a material that simultaneously removes multiple heavy metals and organic matter in a complex environment is more conducive to efficiently solving the problem of water pollution. Summary of the invention

[0004] The purpose of the present invention is to propose a plasma-modified attapulgite / carbon composite material and a preparation method and application thereof. By subjecting the attapulgite / carbon composite material to plasma treatment, the adsorption effect of the attapulgite / carbon composite material on metal ions is improved. The composite material after adsorbing metal ions can also be used as a catalyst for the PDS system. The metal ions will not be dissolved in the system, thereby avoiding secondary pollution, and providing a new idea for the treatment of wastewater containing both heavy metals and antibiotics.

[0005] A method for preparing a plasma-modified attapulgite / carbon composite material comprises the following steps:

[0006] S1. Preparation of preliminary activated attapulgite / carbon composite material (LAK): After mixing industrial alkali lignin and attapulgite evenly, transfer the mixed material to a vacuum tube furnace and stabilize it for 10-60 minutes under the protection of inert gas, heat it to 600°C and pyrolyze it for 1-2 hours to obtain a preliminary activated attapulgite / carbon composite material, which is then sieved through a 200-mesh sieve; wherein the mass ratio of industrial alkali lignin to attapulgite is 1-2:1-7.

[0007] S2. Plasma treatment:

[0008] The initially activated attapulgite / carbon composite material obtained in step S1 is subjected to plasma treatment to obtain a plasma-modified attapulgite / carbon composite material.

[0009] Furthermore, in step S1, the pyrolysis temperature is 600° C. and the pyrolysis time is 2 h.

[0010] Furthermore, in step S1, the heating rate is 5°C / min-15°C / min.

[0011] Further, in step S2, the plasma treatment specifically includes: transferring the preliminarily activated attapulgite / carbon composite material to a plasma tank, fully exchanging the gas with nitrogen, fixing the plasma device, first adjusting the current to 0.1A-0.5A for preheating, adjusting the current to 0.5A-1.5A, treating for 10min-180min, and then stabilizing for 30min-60min.

[0012] The present invention also provides a plasma-modified attapulgite / carbon composite material prepared by the method.

[0013] Furthermore, the present invention also provides the use of the plasma-modified attapulgite / carbon composite material as an adsorbent in the treatment of heavy metal-containing wastewater.

[0014] Furthermore, the heavy metal includes any one of Cu, Cd, Pb and Zn.

[0015] In the present invention, the plasma-treated attapulgite / carbon composite material obtained in step S2 can also be directly used as an adsorbent and catalyst for the PDS system, and applied to wastewater containing heavy metals and antibiotics (e.g., industrial wastewater, pharmaceutical wastewater, and animal husbandry wastewater).

[0016] Furthermore, the heavy metal includes Cu, and the antibiotic is levofloxacin.

[0017] Furthermore, the heavy metals are Cu and Cd.

[0018] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0019] The preparation method of the present invention is simple, and the obtained modified attapulgite / carbon composite material has good adsorption performance for heavy metal ions in wastewater. In addition, the metal ions in the wastewater can be absorbed by the composite material, thereby improving the catalytic efficiency of the composite material in the PDS system and greatly improving the removal rate of antibiotics. In addition, plasma treatment can activate the surface of the material, improve the fixation effect of the material on heavy metals, and reduce the desorption of metal ions.

[0020] The modified attapulgite / carbon composite material of the present invention can simultaneously adsorb multiple heavy metals, and the heavy metals cooperate with the composite material to participate in the activation of PDS, and this process can achieve the purpose of efficiently degrading organic matter. The composite material can not only remove heavy metal pollution in water, but also efficiently degrade organic matter, providing an effective co-removal means for water pollution. It has high practical value and guiding significance. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 XRD patterns of materials with different treatments;

[0022] Among them, (a) base carbon; (b) ATP; (c) DLAK; (d) LAK.

[0023] Figure 2 SEM images of materials with different treatments;

[0024] Among them, (a) LAK; (b) DLAK.

[0025] Figure 3 It is a comparison chart of the removal rates of plasma treated materials and untreated materials in the ternary system.

[0026] Figure 4 The distribution diagram of Cd, Cu and LEV at different pH values;

[0027] Among them, (a) the morphological distribution of Cd at different pH values; (b) the morphological distribution of Cu at different pH values; (c) the morphological distribution of LEV at different pH values.

[0028] Figure 5 The effect of different pH values ​​on the removal efficiency of Cu, Cd and LEV in the ternary system.

[0029] Figure 6 The effect of different attapulgite / carbon composite material dosage on the removal efficiency of Cu, Cd and LEV in the ternary system;

[0030] Among them, (a) the impact on Cd; (b) the impact on Cu; (c) the impact on LEV.

[0031] Figure 7 The effect of different PDS dosage on the removal efficiency of Cu, Cd and LEV in the ternary system;

[0032] Among them, (a) is the impact on LEV; (b) is the impact on Cd; (c) is the impact on Cu; and d is the impact on LEV. DETAILED DESCRIPTION

[0033] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.

[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. It should be noted that the reagents used in the present embodiment are all common commercial products.

[0035] Example 1

[0036] A plasma-modified attapulgite / carbon composite material, the preparation method of which is as follows:

[0037] Industrial alkali lignin and attapulgite were fully mixed in a mass ratio of 2:1. After mixing evenly, the mixed material was transferred to a vacuum tube furnace and stabilized for 30 minutes under the protection of inert gas, and then heated to 600°C at 10°C / min for 2 hours to obtain a preliminary activated attapulgite / carbon composite material (LAK), and the material was sieved through a 200-mesh sieve. The sieved material was transferred to a plasma tank, and after fully exchanging the gas with nitrogen, the plasma device was fixed to adjust the current to 0.1A for preheating, and then the current was adjusted to 1.5A for 30 minutes and then stabilized for 30 minutes to obtain a plasma-activated attapulgite / carbon composite material (DLAK).

[0038] Example 2

[0039] Industrial alkali lignin and attapulgite were fully mixed in a mass ratio of 1:1. After mixing evenly, the mixed material was transferred to a vacuum tube furnace and stabilized for 30 minutes under the protection of inert gas, and then heated to 600°C at 10°C / min for 2 hours to obtain a preliminary activated attapulgite / carbon composite material (LAK), and the material was sieved through a 200-mesh sieve. The sieved material was transferred to a plasma tank, and after fully exchanging the gas with nitrogen, the plasma device was fixed to adjust the current to 0.1A for preheating, and then adjusted the current to 0.5A for 30 minutes, and then stabilized for 30 minutes to obtain a plasma material (DLAK-0.5A).

[0040] Example 3

[0041] Industrial alkali lignin and attapulgite were fully mixed in a mass ratio of 2:7. After being mixed evenly, the mixed material was transferred to a vacuum tube furnace and stabilized for 30 minutes under the protection of inert gas, and then heated to 600°C at 10°C / min for 2 hours to obtain a preliminary activated material (LAK), and the material was sieved through a 200-mesh sieve. The sieved material was transferred to a plasma tank, and after fully exchanging the gas with nitrogen, the plasma device was fixed to adjust the current to 0.5A for preheating, and then adjusted the current to 1.5A for 30 minutes, and then stabilized for 30 minutes to obtain a plasma material (DLAK-1.5A).

[0042] Comparative Example 1

[0043] Based on Example 1, no plasma treatment was performed.

[0044] Performance Testing

[0045] Experimental Example 1

[0046] Effect of plasma treatment on removal rates of LEV, Cu(Ⅱ) and Cd(Ⅱ)

[0047] Experimental conditions: material dosage 0.1 g / L, PDS dosage 5 mM, heavy metal Cd = 300 ppm, Cu = 300 ppm, LEV = 50 ppm, pH = 6, rotation speed 200 rpm, temperature 25°C.

[0048] Figure 3 The removal rates of LEV, Cu(Ⅱ) and Cd(Ⅱ) by LAK and DLAK were compared in the presence of LEV, Cu(Ⅱ) and Cd(Ⅱ). The removal rates of LEV, Cu(Ⅱ) and Cd(Ⅱ) by DLAK in the ternary system were 81.35%, 69.54% and 16.58%, respectively. The removal rates of LEV, Cu(Ⅱ) and Cd(Ⅱ) by LAK in the ternary system were 81.37%, 62.10% and 14.54%, respectively. The removal rate of LEV by DLAK was slightly lower than that of LAK, but the difference was only 0.02%, while the removal rate of Cu(Ⅱ) and Cd(Ⅱ) by DLAK was significantly higher than that of LAK. This is because PDS releases H during the activation of the material. + , so that the heavy metals adsorbed on the surface of the material return to the solution, and the plasma treatment activates the surface of the material, the material's fixation of heavy metals is enhanced, and the metal adsorbed on the surface of the material is effectively inhibited from re-entering the system. Therefore, it can be confirmed that DLAK is better suited for the simultaneous removal of heavy metals and organic matter in the advanced oxidation system.

[0049] Experimental Example 2

[0050] Adsorption performance of DLAK under different pH conditions

[0051] Experimental conditions: material dosage 0.5 g / L, PDS dosage 5 mM, heavy metal Cd = 300 ppm, Cu = 300 ppm, LEV = 50 ppm, pH = 2-6, rotation speed 200 rpm, temperature 25°C.

[0052] Figure 4 The different forms of LEV, Cd(Ⅱ), and Cu(Ⅱ) were shown at pH values ​​ranging from 1 to 14. When the pH value was less than 8, Cd(Ⅱ) was the main form, and when the pH value was less than 6, Cu(Ⅱ) was the main form, which indicated that the removal of Cd(Ⅱ) and Cu(Ⅱ) at pH 2-6 could be attributed to DLAK rather than environmental influences. Figure 5 The removal effect of DLAK on Cu(Ⅱ), Cd(Ⅱ) and LEV under different pH conditions showed that the removal rate changed slowly when the pH value was 4-6. However, when the pH value was less than 3, the removal rate dropped rapidly. This may be due to the presence of a large amount of H + It will compete for adsorption sites on the surface of the material. The surface of the material is protonated and positively charged, and electrostatic repulsion occurs with heavy metal ions, thereby inhibiting the removal performance of DLAK for Cu (Ⅱ) and Cd (Ⅱ). As the pH continues to rise, the repulsion effect decreases and the removal rate increases. For LEV, the removal rate of LEV can be maintained at more than 70% in the range of pH = 2 to 6. This is different from the Fenton system materials that can only exert a good catalytic effect when the pH is less than 3. It also proves that advanced oxidation technology can enable materials to degrade organic matter and remove heavy metals in a wider pH range.

[0053] Experimental Example 3

[0054] Effect of different DLAK dosage on the removal of Cd(Ⅱ), Cu(Ⅱ) and LEV

[0055] Experimental conditions: material dosage 0.1-0.9 g / L, PDS dosage 5 mM, heavy metal Cd = 300 ppm, Cu = 300 ppm, LEV = 50 ppm, pH = 6, rotation speed 200 rpm, temperature 25°C.

[0056] The results are as follows Figure 6As shown. With the increase of DLAK dosage, the removal efficiency of Cd(Ⅱ) and Cu(Ⅱ) increases. This is because the increase in the dosage of the catalyst can provide more adsorption sites and carbonates, which can react with more heavy metal ions, which is conducive to the removal of heavy metal ions. For LEV, the catalyst dosage increases from 0.1g / L to 0.5g / L, and the removal rate will continue to increase with the increase of DLAK dosage; the catalyst dosage increases from 0.5g / L to 0.7g / L, and the removal rate remains unchanged with the increase of DLAK dosage; when the DLAK dosage increases from 0.7g / L to 0.9g / L, the removal rate of DLAK for LEV decreases instead. This is attributed to the fact that the appropriate increase in the catalyst dosage within a certain range helps to provide more catalytic sites to participate in the activation of PDS, so as to produce more active substances and promote the removal of LEV. However, when using excessive catalyst to activate PDS, the excessive catalyst will react with the active substances produced by PDS, thereby reducing the removal rate of LEV and inhibiting the degradation reaction.

[0057] Experimental Example 4 Effect of different PDS dosages on pollutant removal

[0058] Experimental conditions: material dosage 0.5 g / L, PDS dosage 1-9 mM, heavy metal Cd = 300 ppm, Cu = 300 ppm, LEV = 50 ppm, pH = 6, rotation speed 200 rpm, temperature 25 °C.

[0059] The results are as follows Figure 7 As shown. In the absence of PDS, the removal effect of the material on LEV is only 20.35%. At this time, the removal of LEV is the adsorption of LEV by the material. When PDS is added to the system, the removal rate of LEV increases rapidly from 20.35% to 76.02%. This suggests that DLAK has a highly efficient catalytic effect on PDS in the ternary system. As the dosage of PDS increases, the removal rates of heavy metals Cu and Cd decrease (Cu at a dosage of 1mM and 9mM of PDS is 99.96% and 65.63%, respectively, and Cd at a dosage of 1mM and 9mM of PDS is 32.34% and 20.72%, respectively). This may be due to the fact that the process of the material activating PDS to produce active substances will produce H + , H + It will react with the heavy metal substances adsorbed on the surface of the material, causing them to return to the solution system, resulting in a decrease in the removal rate of heavy metals by the material. For LEV, when the PDS dosage changes from 0 to 1mM, the removal rate of LEV changes from 20.35% to 76.03%. This is because after adding PDS to the system, the material activates PDS to produce a large amount of 1Active substances such as O2 have strong oxidizing properties and can effectively decompose LEV. However, when the PDS dosage changes from 1mM to 9mM, the removal rate of LEV only changes from 76.03% to 79.39%. This is because high concentrations of PDS will quench the active substances produced and free radicals and other active substances will quench each other, resulting in the removal efficiency not increasing infinitely.

[0060] Experimental Example 5

[0061] Adsorption performance of DLAK, DLAK-0.5 and DLAK-1.5 on different heavy metal ions

[0062] Experimental conditions: material dosage 0.5 g / L, heavy metal = 300 ppm, pH = 6, rotation speed 200 rpm, temperature 25°C.

[0063] The results are shown in Table 1. DLAK, DLAK-0.5, and DLAK-1.5 materials have good removal performance for most heavy metal ions.

[0064] Table 1

[0065]

[0066] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a plasma-modified attapulgite / carbon composite material, characterized in that: The following steps are involved: S1. Preparation of preliminary activated attapulgite / carbon composite material: After industrial alkali lignin and attapulgite are uniformly mixed, the mixed material is transferred to a vacuum tube furnace and stabilized for 10-60 minutes under the protection of inert gas, and then heated to 600°C for pyrolysis for 1-2 hours to obtain a preliminary activated attapulgite / carbon composite material, which is passed through a 200-mesh sieve; the mass ratio of the industrial alkali lignin to the attapulgite is 1-2:1-7; S2. Plasma treatment: The initially activated attapulgite / carbon composite material obtained in step S1 is subjected to plasma treatment to obtain a plasma-treated attapulgite / carbon composite material.

2. The preparation method according to claim 1, wherein in step S1, the pyrolysis temperature is 600°C and the pyrolysis time is 2 hours.

3. The preparation method according to claim 1, in step S1, the heating rate is 5°C / min-15°C / min.

4. The preparation method according to claim 1, in step S2, the plasma treatment specifically comprises: The initially activated attapulgite / carbon composite material is transferred to a plasma tank, the gas is fully exchanged with nitrogen and then the plasma device is fixed, the current is first adjusted to 0.1A-0.5A for preheating, then the current is adjusted to 0.5A-1.5A for processing for 10min-180min, and then stabilized for 30min-60min to obtain.

5. The plasma-modified attapulgite / carbon composite material prepared by the preparation method according to any one of claims 1 to 4.

6. Use of the plasma-modified attapulgite / carbon composite material according to claim 5 as an adsorbent in the treatment of heavy metal-containing wastewater.

7. The use according to claim 7, characterized in that: The heavy metal includes any one of Cu, Cd, Pb and Zn.

8. Use of the plasma-enhanced attapulgite / carbon composite material according to claim 5 as an adsorbent and catalyst for a PDS system in the treatment of wastewater containing heavy metals and antibiotics.

Citation Information

Cited By

  • Method for treating heavy metals and antibiotics through cooperation of attapulgite / carbon composite material and peracetic acid

    CN120736664A

  • Composite sewage treatment agent

    CN121317928A

  • Accurate regulation and control method and system for pore structure of attapulgite-based material

    CN122076375A